2010
DOI: 10.1007/s00167-010-1093-5
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of open versus arthroscopic Bankart repair using suture anchors

Abstract: Purpose of this study is to conduct a meta-analysis comparing the results of open and arthroscopic Bankart repair using suture anchors in recurrent traumatic anterior shoulder instability. Using Medline Pubmed, Cochrane and Embase databases we performed a search of all published articles. We included only studies that compared open and arthroscopic repair using suture anchors. Statistical analysis was performed using chi-square test. Six studies met the inclusion criteria. The total number of patients was 501,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 23 publications
1
97
0
5
Order By: Relevance
“…In particular, Gerometta et al described that arthroscopic Bankart repair showed favourable results to open repairs: most of the patients returned to the same or higher level of sports after a mean of 9.8 months postoperatively while male and less frequent dislocators (< 6 dislocations) returned significantly faster to their sport and to their preinjury level than female and frequent dislocators (> 10 dislocations), respectively 15 . Petrera et al 16 and Milchteim et al 17 already showed how arthroscopic treatment of shoulder instability represents today not only a valid alternative to open surgery, but absolutely the first choice of treatment, because an arthroscopic repair restores the glenohumeral structures more precisely, reducing bleeding time and infections risk. Furthermore, Wellmann et al 18 demonstrated that arthroscopic surgery for shoulder instability leads to better functional results, especially in a shorter time.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Gerometta et al described that arthroscopic Bankart repair showed favourable results to open repairs: most of the patients returned to the same or higher level of sports after a mean of 9.8 months postoperatively while male and less frequent dislocators (< 6 dislocations) returned significantly faster to their sport and to their preinjury level than female and frequent dislocators (> 10 dislocations), respectively 15 . Petrera et al 16 and Milchteim et al 17 already showed how arthroscopic treatment of shoulder instability represents today not only a valid alternative to open surgery, but absolutely the first choice of treatment, because an arthroscopic repair restores the glenohumeral structures more precisely, reducing bleeding time and infections risk. Furthermore, Wellmann et al 18 demonstrated that arthroscopic surgery for shoulder instability leads to better functional results, especially in a shorter time.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence and revision rates of the arthroscopic Bankart repair were found to be 6 and 4.7%, respectively, in a study. 19 In the past, recurrent instability was often the consequence of capsular redundancy because of ineffective hardware. With modern suture anchors, capsular plication could be done more effectively during the arthroscopic repair.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent retrospective study by Wang et al [11] showed no statistically significant difference in functional outcome between the open vs. arthroscopic groups. Petrera et al [12] performed a meta-analysis comparing the two techniques, the recurrence rate and reoperation rate were lower in patients undergoing arthroscopic treatment, but was not statistically significant. Chalmers P et al [13] through a systematic metaanalysis review concluded that there is no difference between the two techniques in relation to failure rates.…”
Section: Discussionmentioning
confidence: 98%
“…Most authors agree that open surgery should be considered in the presence of certain conditions, such as glenoid bone loss equal or greater than 25%, Hill-Sachs impaction fracture involving more than 30% of the humeral head, even without bipolar injury [6,8,9,12,13]. A careful image evaluation should be performed in order to identify, quantify and characterize these bone defects.…”
Section: Discussionmentioning
confidence: 99%